kansei wire stripper untuk pemilahan sampah kabel di sektor informal - Widyastuti, Widyastuti; Wibowo, Eko Ari; Dicasani, Alifta; Ernawati, Ernawati (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Cables are a rapidly growing type of electronic waste. In the informal sector, metals are commonly extracted from cable waste by melting the insulating layer. It’s simple but generates toxic gases. A safer alternative involves using a wire stripper, that typically used in the cable industry and operated by skilled professionals. However, the informal sector, where most workers are women and daily laborers without specialized skills, requires tools tailored to their specific needs. Unfortunately, such tools are not yet available. This study aims to design a wire stripper suited for the informal sector using the Kansei Engineering Type I method. The identification of kansei words led to a design concept prioritizing safety, durability, and ease of use. Concept mapping produced a wire stripper design with dimensions of 35x30x30 cm, a maximum weight of 5 kg, and an iron body, featuring manually operated splitting and rolling mechanisms.